Financial Behavior of Generation Z in Indonesia: Impact of Literacy, Technology and Lifestyle - Setiawati, Nila Tri; Primadineska, Rasistia Wisandianing (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
This study aims to examine the effect of financial literacy, financial technology, and hedonism lifestyle on financial behavior in Z generation. This study used purposive sampling method to help determine the research sample. The number of samples in this study were 110 respondents. The methods used include descriptive analysis and multiple linear regression analysis. The data used is primary data obtained through distributing questionnaires. Furthermore, the data is processed using SPSS software. The result showed that: 1) financial literacy has a positive and significant effect on financial behavior in generation Z, 2) financial technology has a positive and significant effect on financial behavior in generation Z, and 3) hedonism lifestyle has a positive and significant effect on financial behavior in generation Z. The results of this research imply that the government and financial institutions need to create policies that support the accessibility of financial literacy and services for the younger generation to avoid financial failure and crime in the future.